Pembatasan Kebebasan Perempuan Pada Film Story of Kale: When Someone's in Love dari Lagu I Can't Stop Loving You - Jodi Setiawan (Balai Bahasa Sulawesi Selatan, 2024)
This research aims to explore the representation of women's freedom constraints, the causes of these constraints, and resistance against them The method chosen is qualitative using feminist theory and presenting descriptive analysis. Focusing on the film